2001
DOI: 10.1063/1.1374479
|View full text |Cite
|
Sign up to set email alerts
|

Fowler–Nordheim conduction in polysilicon (n+)-oxide–silicon (p) structures: Limit of the classical treatment in the barrier height determination

Abstract: Articles you may be interested inEllipsometric study of the polysilicon/thin oxide/single-crystalline silicon structure and its change upon annealing Boron penetration and thermal instability of p + polycrystalline-Si/ZrO 2 / SiO 2 /n-Si metal-oxide-semiconductor structures J. Appl. Phys. 91, 65 (2002); 10.1063/1.1419207 Effects of interface roughness and conducting filaments in metal-oxide-semiconductor tunnel structuresFowler-Nordheim current in Si-poly (n ϩ )-SiO 2 -Si(p) structures, with an oxide thickness… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0
2

Year Published

2004
2004
2015
2015

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 53 publications
1
19
0
2
Order By: Relevance
“…7 shows the simulations using u 0 ¼ 2:7 eV and c ¼ À2:9Â10 À3 eV K À1 . This latter value is in close agreement with the temperature coefficient associated with Fowler-Nordheim (FN) conduction in fresh MOS devices ()10 À4 to )10 À3 eV K À1 ) [11]. The connection between SBD and FN was already pointed out in [12] and further explored in [9].…”
Section: Theory and Analysissupporting
confidence: 83%
“…7 shows the simulations using u 0 ¼ 2:7 eV and c ¼ À2:9Â10 À3 eV K À1 . This latter value is in close agreement with the temperature coefficient associated with Fowler-Nordheim (FN) conduction in fresh MOS devices ()10 À4 to )10 À3 eV K À1 ) [11]. The connection between SBD and FN was already pointed out in [12] and further explored in [9].…”
Section: Theory and Analysissupporting
confidence: 83%
“…17 In addition, other effects such as the temperature dependence of the F-N tunneling current, 18,21 the barrier height variation with the oxide thickness, 17,18 and the dependence of the effective mass on oxide thickness, 19,20 may need to be taken into account. Several approximate expressions have been proposed to take into account the temperature dependence 17,18,21,22 and the image force effect. 17 In the present study, for simplicity, we use the above simple expression, i.e., Eqs.…”
Section: Influence Of Nitrogen On Tunneling Barrier Heights and Effecmentioning
confidence: 99%
“…Hadjadj et al 22 obtained barrier heights with respect to temperature changes just by taking a constant effective electron mass of 0.5m e for samples whose thicknesses were changing between 3.5 and 12 nm, and they showed that barrier height was decreased when the temperature was increased.…”
Section: Literature Reviewmentioning
confidence: 99%
“…32 Khairurrijal et al 33 showed from their theoretical calculations that the effective mass of electrons in SiO 2 oxide film increases when the oxide thickness gets decreased, having a value between 0.3m e and 0.9m e . Upon assuming constant electron effective mass at 0.5m e in oxide film, Hadjadj et al 22 added the effect of oxide thickness on electron affinity difference for 5, 7, and 12 nm thick oxides for the temperature ranging from 23 to 300°C. They concluded that not only the temperature but also the oxide thickness had an effect on electron affinity difference and barrier height values under the used assumption of 0.5m e for effective electron mass.…”
Section: ͑8͒mentioning
confidence: 99%
See 1 more Smart Citation